Determinants of Anemia Occurrence in Cervix Ca Patients Undergoing Chemotherapy - Marlina, Rosi; Syaroha, Siti; Pinanggih, Sukma Rahayu; Mulawardana, Pungky; Utomo, Budi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chemotherapy causes the death of some cells that have been formed from the process of DNA, RNA or protein synthesis. The myelosuppressive effects of long-term chemotherapy treatment will continue throughout the therapy cycle such as infection, septicemia and spontaneous bleeding and worsening of anemia. This study aims to determine the factors that influence the occurrence of anemia in cisplatin chemotherapy patients. This study used an analytical observational design with a retrospective cross-sectional approach (medical records). The population was 394 patients with a sample of 136 with a simple random sampling technique. Data were obtained from medical records and supporting examination results, then summarized and tabulated according to the coding. Data analysis used the chi square test. The results of this study obtained 86 patients who experienced anemia and as many as 136 cases of anemia with 35 patients experiencing recurrent anemia. The p value in the chi-square test for age with the occurrence of anemia was (p = 0.026), the p value in the chemotherapy series (p = 0.011), the p value in leukopenia with anemia (0.000), the p value in thrombocytosis (p = 0.004). The use of chemotherapy with cisplating has a significant relationship with anemia in patients with Ca Cervix IIIA - IVA. The use of chemotherapy with cisplatin has a significant relationship between age, leukopenia levels, thrombocytosis levels, and the series of chemotherapy used in the occurrence of anemia. So that chemotherapy can cause damage to the spinal cord, so that it fails to produce red blood cells, white blood cells, and platelets in the blood.